Sebuah Analisis Formulasi Strategi Perusahaan Menggunakan Metode Quantitative Strategic Planning Matrix (QSPM) : (Studi Kasus: Resort Hotel di Anyer) - Fazya Fani Ramandha (Journal of Optimization System and Ergonomy Implementation, 2023)
Resort Hotel Anyer is a star hotel with a resort type which is located close to several other star hotels which offer various different service quality standards. Resort Hotel Anyer has not been able to compete with existing competitors, resulting in income and the number of tourist visits to Resort Hotel Anyer becoming very unstable due to limited market share. Therefore, it is necessary to design a company strategy to find out what strategy is most suitable to be implemented. The methods used in this research are the IFE matrix, EFE matrix, IE matrix, SPACE matrix, SWOT matrix, and QSPM. The research results showed 16 strengths, 5 weaknesses, 10 opportunities and 7 threats. The position of the Anyer Hotel Resort, in the IE matrix, is in quadrant IV in the grow and build category and in the SPACE matrix it is in quadrant I in the aggressive category. By using the SWOT matrix, 12 alternative strategies were obtained. From 12 alternative strategies, the most suitable strategy was selected using QSPM. The highest Sum Total Attractive Score was obtained at 5.06, namely the strategy of carrying out business development of the facilities owned, analyzing prices, room quality, number of human resources by benchmarking competitors.